Implementasi Hadis Dalam Hukum Sosial dan Politik - Moh. Tamimi (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2020)
This article aims to discuss the implementation of Prophetic traditions (hadith) on law, social, and politic as part of the integration of science and religion . On this integration, hadith as a part of Islamic traditions emulsified its value with social and political aspects. Social sciences may in part coloring the interpretation of Hadith to formulate more contextual meaning that has been applied in various times and places..